The moderating role of influence tactics on cultural intelligence and expatriate success - Ng, Siew Imm; Tan, Wai Yee (Universiti Putra Malaysia Press, 2013)
As a result of globalization, expatriate numbers have increased significantly, making expatriation failure one of the top concerns of International Human Resource Managers to curb. This study looks at the potential of using Cultural Intelligence and Influence Tactics in explaining expatriate success. Eighty three expatriates, mainly from Singapore, Thailand, Philippines, Indonesia, Japan, and Korea, working with a US-based MNC in the Klang Valley, Malaysia, participated in this study. At least four interesting findings were discovered: First, evidence that expatriates that are culturally intelligent in motivational and behavioural aspects, tended to perform better in their work; Second, high CQ expatriates, who used more Upward Appeal influence tactic, seemed to achieve lower Job Performance; Third, expatriates, who were culturally intelligent motivationally, were found to adjust to Malaysia more effectively. Finally, those high CQ expatriates who used more Rational Persuasion Influence Tactics adjusted to work and social life better in Malaysia.